2015
DOI: 10.1016/j.bcmd.2014.07.009
|View full text |Cite
|
Sign up to set email alerts
|

DEK oncogene expression during normal hematopoiesis and in Acute Myeloid Leukemia (AML)

Abstract: DEK is important in regulating cellular processes including proliferation, differentiation and maintenance of stem cell phenotype. The translocation t(6;9) in Acute Myeloid Leukemia (AML), which fuses DEK with NUP214, confers a poor prognosis and a higher risk of relapse. The over-expression of DEK in AML has been reported, but different studies have shown diminished levels in pediatric and promyelocytic leukemias. This study has characterized DEK expression, in silico, using a large multi-center cohort of leu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
(40 reference statements)
1
12
0
1
Order By: Relevance
“…The expression of DEK has long been considered upregulated also in AML, based on two studies using quantitative PCR analysis to demonstrate overexpression in cohorts of 15 and 41 patients [7,8]. However, in a recent study in this journal, Logan et al showed similar expression levels in normal and malignant hematopoietic cells in an in silico analysis of a large pre-existing dataset, verified by tissue microarray [9].…”
Section: To the Editormentioning
confidence: 99%
“…The expression of DEK has long been considered upregulated also in AML, based on two studies using quantitative PCR analysis to demonstrate overexpression in cohorts of 15 and 41 patients [7,8]. However, in a recent study in this journal, Logan et al showed similar expression levels in normal and malignant hematopoietic cells in an in silico analysis of a large pre-existing dataset, verified by tissue microarray [9].…”
Section: To the Editormentioning
confidence: 99%
“…Aberrant expression or localization of the DEK DNA-binding protein has been associated with several diseases, including acute myeloid leukemia (Logan et al 2015, Von Lindern et al 1992), various types of solid tumors (Piao et al 2014, Privette Vinnedge et al 2015, Wang et al 2014), and as an auto-antigen in numerous auto-immune diseases, most notably juvenile idiopathic arthritis (Mor-Vaknin et al 2011, Sierakowska et al 1993, Szer et al 1994). DEK (human 6p22.3) is a unique protein, with no known homologs, that preferentially binds supercoiled and cruciform DNA in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…Upon examination of DEK mRNA levels in HSCs/HPCs and mature myeloid lineage cells, it was discovered that DEK expression was elevated in HSCs and HPCs when compared to mature granulocytic and monocytic populations in both human and mice [1, 43]. However, peak DEK expression levels varied between mice and man [1]. The greatest DEK expression in humans occurred in HSCs with a steady decline in expression levels as the cells differentiated into HPCs then matured into polymononuclear cells (PMNs) and monocytes.…”
Section: Dek and Hematopoiesismentioning
confidence: 99%
“…DEK was originally discovered as part of the fusion protein DEK-NUP214 (i.e. DEK-CAN), a result of a t(6;9) chromosome translocation in a subset of patients with acute myelogenous leukemia [14*], and as an oncoprotein in various neoplasms including melanoma [57*], breast cancer [8], glioblastoma [9], hepatocellular carcinoma [10, 11*], retinoblastoma [12, 13], gastric adenocarcinoma [14*], non-small cell lung cancer [15*], pancreatic ductal adenocarcinoma [16*], and bladder cancer [17]. DEK was found to be a regulator of hematopoiesis controlling HSC and HPC numbers/fate decision [18, 19].…”
Section: Introductionmentioning
confidence: 99%